Pelajar Cerdas Tanpa Kekerasan: Membangun Keterampilan Resolusi Konflik di Sekolah Menengah Atas Negeri 7 Kota Malang - Sembiring, Ruth Agnesia; Setiawan, Andi; Subekti, Tia (Universitas Nusantara PGRI Kediri, 2025)
Conflict is an integral part of social life, including in the school environment. Interactions between students from diverse social and cultural backgrounds and with different personalities often lead to conflict. If not managed properly, conflict in the school environment can result in aggressive behavior, bullying, and other acts of violence. Schools, as educational institutions, play a strategic role in shaping the character and social skills of students. One approach that can be applied is conflict resolution education, which focuses on developing communication skills, empathy, and peaceful problem-solving (Deutsch et al., 2016). Based on this urgency, this community service program aims to provide conflict resolution skills training for students at SMA Negeri 7 Kota Malang. The main target of this activity is 10th grade students so that they have effective conflict resolution skills to create a safe and conducive learning environment. The material provided covers the causes of conflict and Simon Fisher's five quadrants of conflict resolution, namely Avoiding, Dominating, Accommodating, Problem Solving/Collaborating, and Compromising (Fisher et al., 2001). By equipping students with these skills, they are expected to be able to resolve disputes constructively without resorting to violence. Conflict resolution educational interventions in schools can reduce aggressive behavior and increase positive relationships between students. Conflict resolution skills also contribute to building a more inclusive and harmonious school culture.